Insights into beta cell regeneration for diabetes via integration of molecular landscapes in human insulinomas - Huan Wang (Nature Portfolio, 2017)
Diabetes results in part from a deficiency of functional pancreatic beta cells. Here, the authors study the genomic and epigenetic landscapes of human insulinomas to gain insight into possible pathways for therapeutic beta cell regeneration, highlighting epigenetic genes and pathways.